Die doppelte Aphrodite - alt und neu bei griechischen Kultbildern - Schoch, Karen (Universitätsverlag Göttingen, 2010)
Since the 5th century b. c., archaistic figures were used as a pillar for the statues of Aphrodite and later sometimes also for other gods. The question of design and interpretation is topic of this work. The characteristics of gods were always shown in their body image and posture. To that effect Aphrodite was pictured in a casual and sensual way with a very feminine body shape. The archaistic pillar could be a way to show that nevertheless Aphrodite was a venerable goddess.